Characterization And Forecasting The Performance Of Generation Z In The Framework Of Strengthening The Usefulness Of The Demographic Bonus In Fakfak District - Muhamat Arku Maswatu; Risyana Mirda; Suprijono Wihel; Rifda Fitranti (Sean Institute, 2024)
The transfer of life spans between generations certainly leaves challenges regarding the importance of leadership and managerial skills in managing sustainable development. Generation Z is expected to be the party who can accelerate the development process. Generation Z lived and grew to become the new owners of the earth at a time when generation Y had left behind a pile of hope for technological progress in the form of digital transformation. Study aim For know various characteristics And forecasting performance generation Z in frame strengthening Power use the demographic bonus in the Regency Fakfak . Descriptive research method with a quantitative analysis approach. Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. The research results are presented in the form of a spider web diagram and a regression equation model obtained from the SPSS version 2.3 statistical tool.